Non-invasive epigenetic detection of fetal trisomy 21 in first trimester maternal plasma. - Ji Hyae Lim; Shin Young Kim; So Yeon Park; Shin Yeong Lee; Mi Jin Kim; You Jung Han; Si Won Lee; Jin Hoon Chung; Moon Young Kim; Jae Hyug Yang; Hyun Mee Ryu (PLoS ONE, 2011)
BACKGROUND: Down syndrome (DS) is the most common known aneuploidy, caused by an extra copy of all or part of chromosome 21. Fetal-specific epigenetic markers have been investigated for non-invasive prenatal detection of fetal DS. The phosphodiesterases gene, PDE9A, located on chromosome 21q22.3, is completely methylated in blood (M-PDE9A) and unmethylated in the placenta (U-PDE9A). Therefore, we estimated the accuracy of non-invasive fetal DS detection during the first trimester of pregnancy using this tissue-specific epigenetic characteristic of PDE9A. METHODOLOGY/PRINCIPAL FINDINGS: A nested, case-control study was conducted using maternal plasma samples collected from 108 pregnant women carrying 18 DS and 90 normal fetuses (each case was matched with 5 controls according to gestational weeks at blood sampling). All pregnancies were singletons at or before 12 weeks of gestation between October 2008 and May 2009. The maternal plasma levels of M-PDE9A and U-PDE9A were measured by quantitative methylation-specific polymerase chain reaction. M-PDE9A and U-PDE9A levels were obtained in all samples and did not differ between male and female fetuses. M-PDE9A levels did not differ between the DS cases and controls (1854.3 vs 2004.5 copies/mL; P = 0.928). U-PDE9A levels were significantly elevated in women with DS fetuses compared with controls (356.8 vs 194.7 copies/mL, P<0.001). The sensitivities of U-PDE9A level and the unmethylation index of PDE9A for non-invasive fetal DS detection were 77.8% and 83.3%, respectively, with a 5% false-positive rate. In the risk assessment for fetal DS, the adjusted odds ratios of U-PDE9A level and UI were 46.2 [95% confidence interval: 7.8-151.6] and 63.7 [95% confidence interval: 23.2-206.7], respectively. CONCLUSIONS: Our findings suggest that U-PDE9A level and the unmethylation index of PDE9A may be useful biomarkers for non-invasive fetal DS detection during the first trimester of pregnancy, regardless of fetal gender.